Pengelolaan Lingkungan melalui Gotong Royong dan Bank Sampah Botol Plastik di Kelurahan Margahayu - Achmad Muhazir; Yesta Sadha Syahputra; Rizki Nur Wakhid; Muhamad Idrus Satria; Teguh Prasetyo; Arista Binarsih; Mohammad Haikal; Nadip Fajar Vidianto; Dimas Aditya Nugraha; Andre Satrio Trihantono; Annisa Oktaviani; Achmad Yasril (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
The environment is one of the important aspects that can support the survival of living things. One of the environmental challenges in Margahayu Village is the accumulation of plastic waste, particularly plastic bottles, whose numbers continue to rise and have a detrimental impact on the environment. The environment is the responsibility of both the community and the government to ensure access to a healthy lifestyle. The methods employed in this community service initiative are one way to help improve the quality of life for the community and strengthen their capacity to address various challenges in their daily lives. One way to improve the quality of life of the community and enhance their ability to face daily challenges is by using a community service approach known as community empowerment. Students collaborate with the Margahayu Village community, particularly in Kp. Rawa Semut, to create a container or what is known as the Plastic Bottle Waste Bank. This initiative aims to help the community convert plastic bottle waste into a marketable commodity. With the hope that the community can sort waste and maintain a clean environment free from plastic bottles that are difficult to decompose. Based on the discussion results in line with the proposed title, it can be concluded that students collaborated with the Margahayu village community, specifically in RW 012, to carry out community service and planting activities around the park area. This initiative aimed to improve the health quality of the surrounding community in preparing for the dengue fever season and to clean up waste piles.